How to Win in Modern Electoral Campaigning. Issue 1 (June 2013) - Strohmeier, Gerd
The article contributes a macro-political perspective to some questions dealing with voting behaviour in modern democracies, the patterns of an ideal electoral campaign, the factors which are able to decide an election, and the 'dos' and 'don'ts' in electoral campaigning. It (1) draws up a typology of voters based on party affiliation and rationality; (2) discusses the requirements of electoral campaigns which differ with the political system, the type of political party, the present position of the party or the candidate in the political system and current topics; (3) addresses the impact of the different elements of the 'political product'–-the party, the programme and the candidates–-and the audiences of the different communication channels in an electoral campaign and (4) approaches how modern electoral campaigns deal with the electorate and the political opponents.